Cabot launches next-gen black styrene acrylonitrile masterbatch. Issue 12 (December 2020) - Unknown
Abstract : Massachusetts-based specialty chemicals company Cabot Corporation has launched the Plasblak® XP6801D black masterbatch, a next-generation styrene acrylonitrile (SAN)-based formulation that meets the needs of the styrenics market without any trade-off between colour and mechanical properties. Plasblak XP6801D enables excellent colour performance, mechanical properties and UV resistance at a lower masterbatch concentration.